2005
DOI: 10.1186/1471-2458-5-50
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of episodic adenolymphangitis: a longitudinal prospective surveillance among a rural community endemic for bancroftian filariasis in coastal Orissa, India

Abstract: BackgroundThe epidemiological knowledge on acute condition of lymphatic filariasis is essential to understand the burden and issues on management of the disease.MethodsA one year long longitudinal prospective surveillance of acute adenolymphangitis (ADL) was carried out in rural population of Orissa, India.ResultsThe annual incidence of ADL per 1000 individuals is 85.0, and is slightly higher (P > 0.05) in male (92.0) than in female (77.6). A steady rise in the incidence of ADL episodes along with the age is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Our results showed that the incidence density of AFM remained stable following the first two MDAs, though the rates remained twice that reported from other LF endemic regions such as Tanzania [20], India [21] and Ghana [22]. AFM events in the latter phases of our study (post MDA years 3 and 4), when village-specific microfilaria levels and mosquito transmission of infective larvae were reduced respectively by 89–98% and 84–97% relative to the pre-MDA values [24], may be attributed to active LF infections that were not cured by earlier MDAs, pre-existing chronic LF pathology, and/or continued exposure to infective larvae [9], [10], [12].…”
Section: Discussionsupporting
confidence: 55%
“…Our results showed that the incidence density of AFM remained stable following the first two MDAs, though the rates remained twice that reported from other LF endemic regions such as Tanzania [20], India [21] and Ghana [22]. AFM events in the latter phases of our study (post MDA years 3 and 4), when village-specific microfilaria levels and mosquito transmission of infective larvae were reduced respectively by 89–98% and 84–97% relative to the pre-MDA values [24], may be attributed to active LF infections that were not cured by earlier MDAs, pre-existing chronic LF pathology, and/or continued exposure to infective larvae [9], [10], [12].…”
Section: Discussionsupporting
confidence: 55%
“…Lymphedema severity was established based on the seven stage classification system developed by Dreyer, et al [16]. ADL episodes were defined as any period of pain, redness, and/or swelling of the affected leg, which may have been accompanied by fever and/or chills [18, 19]. …”
Section: Methodsmentioning
confidence: 99%
“…The duration of ADLA, primarily based on patient self-reporting, ranges from 1 to 16 days [21,32,39-46,48,49,51,52] (Table 1). Recurrent ADLA episodes result in significant short-term disability, and are of much greater concern to patients than is lymphoedema per se [53].…”
Section: Acute Inflammatory Episodes (Acute Attacks)mentioning
confidence: 99%